Internal Migration, Social Exclusion, and Victimization: An Analysis of Chinese Rural-to-Urban Migrants. (July 2017) - Zhong, Hua; Xu, Jianhua; Piquero, Alex R.
Objectives: This article applies a multidimensional social exclusion framework to examine Chinese rural-to-urban migrant victimization. Method: Data from the 2012 China Labor Dynamics Survey is used to examine whether Chinese migrants are more likely to be victimized compared to urban residents and to what extent the prior findings on the meditating roles of social exclusion between immigration and victimization can be applied to understand Chinese migrants' victimization. Results: Findings reveal the elevated victimization risks among nationwide rural-to-urban migrants. Logistic regression models find that social exclusion mediates the link between migrant status and victimization and that social exclusion predicts victimization. Conclusions: The discriminative institutional arrangements in China are a major force of the universal disadvantages of Chinese migrants. That is, it is not the migrant status itself, but the social exclusion suffered by individuals that increase the likelihood of being criminally victimized.